2022
DOI: 10.3389/fmed.2022.849677
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Abnormalities in the Small Intestine of Zambian Children With Stunting

Abstract: BackgroundEnvironmental enteropathy (EE) contributes to impaired linear growth (stunting), in millions of children worldwide. We have previously reported that confocal laser endomicroscopy (CLE) shows fluorescein leaking from blood to gut lumen in vivo in adults and children with EE. We set out to identify epithelial lesions which might explain this phenomenon in Zambian children with stunting non-responsive to nutritional support.MethodsWe performed confocal laser endomicroscopy (CLE) in 75 children and colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The surface area of the intestine is hugely magnified by three levels of amplification: valvulae conniventes (folds visible to the naked eye), villi, and microvilli. In EE the villus surface area is reduced by villus blunting and fusion, and the microvilli are damaged (22). Consequently, we anticipated being able to detect this reduced surface area in Zambian adults from a community which we have shown in previous studies to have near-ubiquitous enteropathy (3, 27, 28) compared to British adults.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The surface area of the intestine is hugely magnified by three levels of amplification: valvulae conniventes (folds visible to the naked eye), villi, and microvilli. In EE the villus surface area is reduced by villus blunting and fusion, and the microvilli are damaged (22). Consequently, we anticipated being able to detect this reduced surface area in Zambian adults from a community which we have shown in previous studies to have near-ubiquitous enteropathy (3, 27, 28) compared to British adults.…”
Section: Discussionmentioning
confidence: 91%
“…Nutrient digestion and absorption are important domains of small intestinal function and direct measurement may help in quantifying functionally important malabsorption. SI is an enterocyte-specific, brush-border enzyme that is maximally expressed as enterocytes mature and migrate to the top of the villus (21) and the villus blunting and microvillus damage observed in EE would suggest that SI is a good potential diagnostic target (18,22). Previous work in Zambian children has also demonstrated that gene expression of sucraseisomaltase is lower in stunted children (and markedly lower in severe acute malnutrition) compared with adults and expression of glucose transport enzymes (SLC5A1) appears to be upregulated in EE (23).…”
Section: Discussionmentioning
confidence: 99%
“…The suite of growth factors detected in children with SAM could reflect an attempt to restore normal barrier function or increase tissue growth ( 21 ). The extent of epithelial damage in SAM is marked ( 13 ), and can be directly visualised in the gut of adults with environmental enteropathy as plumes of effluxing fluorescein using confocal laser endomicroscopy ( 30 , 31 ). We posit that an inadequate growth factor response in the face of intestinal damage and persistent inflammation reflects a lack of epithelial repair, which permits further inflammatory damage and tissue remodelling, and ultimately drives mortality or poor growth recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Paneth cells may be implicated in the pathogenesis of EED. A recent study of small intestinal biopsies from Zambian children with EED complicated by growth stunting were found to have depleted Paneth cells and goblet cells compared with control (non-EED) biopsies [34 ▪ ]. The resulting impairment in secretory function may compromise intestinal barrier function, further perpetuating the intestinal inflammation characteristic of EED.…”
Section: Environmental Enteric Dysfunctionmentioning
confidence: 99%